PRAKTIKALITAS MODUL PENDIDIKAN SADAR WISATA SEBAGAI EDUKASI SOSIAL BAGI PENGELOLA OBJEK WISATA BERBASIS MASYARAKAT DI KABUPATEN BIREUEN PROPINSI ACEH (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2023)
This research started from the problem of low public awareness of cultural tourism objects to participate in preserving sustainability, lack of cooperation in developing cultural tourism objects, and limited training for tourism object managers. The research objective is to describe the practicality of the tourism awareness education module as social education for community-based tourism object managers. The type of research is R&D using the ADDIE model. The development subjects in this study were the tourism awareness group of the Lapan Syuhada Cemetery in Blang Tambue Village, Bireuen Regency, which consisted of 20 people. Sampling using incidental sampling technique. Data collection techniques using observation, interviews, and documentation. Data analysis techniques use percentages. The results of the study show that the tourism awareness education module is classified as practical as social education for community-based tourism object managers in terms of; 1) The results of observer observations on the process of using modules as teaching materials have been carried out well, where students have understood the steps of learning activities, understand various concepts in modules, are interested in reading modules. 2) The results of learning activities using the module are very good, 3) the response of students to the module is very good